Eulerian solver sensitivity for computing long-duration blast drag loading on columns. Issue 1 (21st March 2022) - Cannon, Laura; Denny, Jack; Clubley, Simon
Abstract : 'Long-duration' blast waves can exert damaging drag loads on finite structural columns that are complex to characterise. In the absence of suitable drag coefficients, computational fluid dynamics (CFD) can be the only satisfactory approach for calculating blast loading. Commercially available CFD software with shockwave modelling capabilities require solving the Euler equations that assume inviscid flow. Two Eulerian solver types are generally used: Godunov and flux-corrected transport, the latter of which is commonly perceived as more accurate for shockwave problems. This study investigates the capability of both solvers for calculating drag loading from long-duration blast interaction with an I-section, verified through comparison to experimental measurements. No solver sensitivity was observed for pressures on exposed geometry surfaces, although discrepancies were observed for shielded surfaces, particularly during later stage interaction. The Godunov scheme demonstrated increased computational efficiency and reliability in comparison to the flux-corrected transport solver type, generating results in better agreement to experimental data. The results provided new understanding of solver sensitivity for modelling long-duration blast drag loading on finite targets using Eulerian CFD analyses.